2013
DOI: 10.11003/jkgs.2013.2.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Combined Positioning Accuracy using GPS and GLONASS Navigation Satellites

Abstract: Due to inaccurate safe navigation estimates, maritime accidents have been occurring consistently. In order to solve this, the precise positioning technology using carrier phase information is used, but due to high buildings near inland waterways or inclination, satellite signals might become weak or blocked for some time. Under this weak signal environment for some time, the GPS raw measurements become less accurate so that it is difficult to search and maintain the integer ambiguity of carrier phase. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results indicated that the 'GPS+GLO' combination had a larger RMS value for the position error than 'GPS-only'. Choi et al (2013) reported that the GPS and GLONASS combination did not show improved positioning performance within the Korean Peninsula compared to GPS-only positioning. These results of the present study are consistent with the results of the previous study.…”
Section: Resultsmentioning
confidence: 97%
“…The results indicated that the 'GPS+GLO' combination had a larger RMS value for the position error than 'GPS-only'. Choi et al (2013) reported that the GPS and GLONASS combination did not show improved positioning performance within the Korean Peninsula compared to GPS-only positioning. These results of the present study are consistent with the results of the previous study.…”
Section: Resultsmentioning
confidence: 97%